A Systematic Review of the Performance of Methods for Identifying Carious Lesions - James D. Bader, DDS, MPH; Daniel A. Shugars, DDS, PhD; Arthur J. Bonito, PhD (2002)
This systematic review evaluates evidence describing histologically validated performance of methods for identifying carious lesions. A search identified 1,407 articles, of which 39 were included that described 126 assessments of visual, visuaVtactile, radiographic (film and digital), fiber optic transillumination, electrical conductance, and laser fluorescence methods. A subsequent update added four studies contributing 10 assessments. The strength of the evidence was judged to be poor for all applications, signifying that the available information is insufficient to supporf generalizable estimates of the sensitivity and specificity of any given application of a diagnostic method